Peningkatan Sumber Daya Masyarakat Desa dalam Binaan Pusat Kegiatan Belajar Masyarakat (PKBM) - Vethy Octaviani; Sri Narti; Syisva Nurwita (Universitas Mathla'ul Anwar Banten, 2018)
IMPROVING RESOURCES OF VILLAGE SOCIETY IN COMMUNITY LEARNING ACTIVITY CENTER. The lack of productivity and economic activity carried out by the community is caused by the lack of knowledge and skills possessed. Thus, the Community Learning Activity Center (PKBM) was established as a community-based education tool. PKBM Alena Smart School in Tebat Monok Village and PKBM Az-Zahir in Talang Karet Village are two of several PKBM in Kepahiang Regency. PKM team and both of PKBM are together as partners make efforts to improve community skills and improvement of education services through training and advisory methods aimed to improve the quality of production, management and marketing with an expectation of achieving economic and educational improvements that lead to improving the welfare of Tebat Monok and Talang Karet Village Community. The result of the activity that has been achieved is the formation of a small industry managed by the community of Tebat Monok in the guidance of PKBM Alena Smart School which is focused on making handicraft and handmade with trademark of Tebat Monok Thonksys Galery And Craft. As for the Talang Karet village community, the business is focused on processed foods with trademarks of Talang Karet Thonksys Cake's. For the business able to run well, team also created the training and assistance in the field of management for administration and for direct marketing activities, team created the activity about to makin display in PKBM Location and created the promotion bay the sosial media instagram. Other than that, PKM activities are also carried out to improve education services in both PKBM so that the equalization of Package A, B, and C in PKBM Alena Smart School and guidance in PKBM Az-Zahir becomes more comfortable, which is also supported by the Park Community Reading.